The Illocutionary Speech Acts of the Statistics for Language Research Course on Learning Management System - Marsevani, Maya; Tohmi, Nantakarn; Nugraha, Hendra (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
In the post-COVID-19 era, lecturers frequently employ internet tools to facilitate learning. However, the majority of speech act research to date has been conducted using data from online learning platforms such as Learning Management Systems (LMS) or Microsoft Teams. Therefore, this study aims to investigate the occurrence of illocutionary speech acts used by lecturers in the Statistics for Language Research course. Descriptive qualitative research was employed in this study to analyze data obtained from the speech characteristics in messages posted in the Statistics for Language Research (SLR) course on the LMS and conversations between the lecturer and students recorded on Microsoft Teams. Data analysis was conducted based on the speech acts theory from Searle (1969). The study's findings showed that the courses employed four different illocutionary speech patterns. The study's findings revealed that the courses utilized four distinct illocutionary speech patterns. The most frequent occurrences were noted in assertive, expressive, directive, and commissive speech acts. From the data, it is evident that assertive speech acts are the dominant type. Furthermore, commissive speech acts were involved in the LMS, primarily focusing on scheduling plans for class. To conclude, it is implied that the recordings highlighted assertive speech acts as the dominant type, which was mainly utilized for explaining materials to students.